Demographic differences in the travel Behaviour: Case Study of regional route in Iraq. Issue 1 (March 2020) - Al-Taweel, Hayder Mohammed; Al-Bdairi, Ahmed Shaker; Al-Ridha, Ahmed S. D.; Yousif, M. Yousif
Abstract: Objective: The aim of this work is to the relation between age, and gender and choosing a certain mode of transport to travel between two main Iraqi cites. Methods: a statistical method, T-test, is used to distinguish between these parameters. Data: Infield survey data was collected using questionnaire. Results: the results indicate that passengers are differentiated in terms of age, and gender. For instance 1-As age of male traveler increased, participants were more likely to travel by train than other mode of transport. 2-As age of female traveler increased, participants were more likely to travel by small vehicles than other mode of transport.